Potensi Aktivitas Antioksidan Fraksi Etanol Rotan Jernang Daemonorops Draco - Vindi Annisa Rahmah; Nafisah Amri; Becek Hamisah (Journal on Education, 2025)
Jernang rattan (Daemonorops draco) is used traditionally as treatment for various health problems. One of them is degenerative diseases caused by free radicals,such as cancer. A natural alternative that able to overcome this disease needs to be developed. Scientifically, jernang rattan is known to have variety of secondary metabolites such as flavonoids,terpenoids,and alkaloids that cause abundant pharmacological activity in it. This makes jernang rattan to be potential as an antioxidant or anticancer compound. Research began with the extraction of compounds using maceration methods with ethanol solvents. Yield of the thick extract obtained was 9,912%. Phytochemical analysis was carried out to determine the content of compounds in extract. It results that extract showed the presence of flavonoid,triterpenoid and alkaloid compounds. Vacuum column chromatography(KVC) is then carried out to simplify the compounds contained in extracts. From this stage 5 combined fractions were obtained which were then tested for antioxidant (DPPH method). The test results of antioxidant activity on the ethanol extract gave an IC50 value of 212,235. Meanwhile, the fraction shows better IC50 value of 32,807.